Pelletizing device for improving tantalum powder performance and application thereof
By improving the performance of powder performance, the method of multiple spray, multiple grains and multiple screening is adopted to solve the inadequate distribution of the existing technologies and the granular distribution caused by the long granularity time caused by the long granularity time. The unequal problem has achieved the low pink powder rate and narrow particle size distribution, which improves the performance of the electrolytic capacitor.
Patent Information
- Application Number
- CN202411484914.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-28
AI Technical Summary
The existing tantalum powder pelletization methods have problems such as uneven distribution of pelletizing agents, uneven distribution of particle sizes, and high fine powder rate, which leads to large leakage current of the anode block, which affects the voltage withstandability of the tantalum electrolytic capacitors. Reliability and stability.
The group -based device that improves the performance of the powder, which includes the spray device and the granularity device. Through multiple spraying, multiple grain, and multiple screening methods, the mixing method of the group chemical agent is changed, and sprayed evenly. Persons and granules are carried out to avoid uneven particle size distribution caused by the uneven distribution of the ball.
Increasing the degree of uniformity of the two particle particles, reducing the proportion of-400 mesh powder fine powder, increased the loosening density of the pink, enhanced the breakdown voltage of the electrolytic capacitor, reduced the leakage current, increased the current, improved The capacity, reliability and stability of the capacitor.
Smart Images

Figure CN119368731A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of capacitor preparation, and in particular relates to a pelletizing device for improving the performance of tantalum powder and an application thereof. Background Art
[0002] Tantalum electrolytic capacitors are widely used in various types of mid-to-high-end electronic equipment manufacturing, such as automotive electronics, aerospace, weapons and equipment, and ships, due to their high reliability, large capacity, and long life. The anode film made of tantalum has stable chemical properties (especially in acidic electrolytes) and high resistivity (7.5×10 10 Ω·cm), large dielectric constant (27.6), and small leakage current. In the manufacturing of capacitors, the annual demand in the world is more than 30 billion, and the annual demand in my country alone is more than 6 billion. It is a core basic component product with a large market demand.
[0003] Tantalum powder is the main anode material of tantalum electrolytic capacitors, and its quality directly affects the performance of tantalum electrolytic capacitors. Among the processes for preparing tantalum powder, the potassium sodium fluorotantalate reduction method and the mechanical method are the two most widely used and most mature processes for producing capacitor-grade tantalum powder. The former is mainly used to produce low-voltage and high-specific capacitance tantalum powder, while the latter is mainly used to produce medium- and high-voltage low-specific capacitance tantalum powder. Compared with the coral-shaped tantalum powder prepared by the sodium reduction method, the tantalum powder prepared by the mechanical method has a simpler particle shape, better pressure resistance, and higher reliability. The mechanical method is currently the most widely used and most mature process for producing capacitor-grade medium-voltage flake tantalum powder.
[0004] The basic process of the mechanical process is to use sodium reduced tantalum powder or tantalum powder crushed by hydrogenation as the main raw material, stainless steel balls as ball milling media, anhydrous ethanol as ball milling agent, and after a certain period of ball milling, coral-shaped or granular tantalum powder is prepared into flaky tantalum powder. The ball-milled tantalum powder is washed with water and acid washed to remove chemical impurities in the tantalum powder, annealed by heat treatment, pelletized by pelletization, and oxygen reduction process to reduce its oxygen content. The combination of one or more of the above processes can obtain the final capacitor-grade tantalum powder.
[0005] The flaky tantalum powder prepared by mechanical method has the disadvantages of poor fluidity and formability. There are two reasons for the poor fluidity and formability of flaky tantalum powder: first, due to the influence of the microscopic morphology of the particles, the tantalum powder after ball milling is scaly or leaf-shaped. Compared with coral-shaped or spherical tantalum powder, the friction between the flaky particles is larger, so the fluidity is poor; second, because the tantalum powder undergoes a large grinding effect during the ball milling process, the primary or secondary particles of the tantalum powder particles will deform, break, and fragment under the action of external stresses such as shear, impact, and compression, which further reduces the size of the primary particles after ball milling, resulting in an increase in fine powder after ball milling. The harm of fine powder in tantalum powder can be manifested in both physical properties and electrical properties. In terms of physical properties, the increase of fine powder in tantalum powder makes its fluidity and pressing performance worse; in terms of electrical properties, fine powder has an adverse effect on the electrical properties of the anode block. More fine powder leads to a larger leakage current of the anode block, which reduces the withstand voltage performance, reliability, and stability of tantalum electrolytic capacitors.
[0006] In order to improve the physical properties of flaky tantalum powder, pelletization is generally used to agglomerate particles in the medium-pressure tantalum powder preparation process. It is a common practice to agglomerate particles with smaller particle sizes into larger secondary particles, reduce the proportion of fine powder in tantalum powder, and improve the performance of tantalum powder. In this regard, tantalum powder producers have done a lot of work on the pelletization of tantalum powder.
[0007] Japanese patent JP3105294B2 proposes a method for granulation using a fluidized bed granulator. This method is to prevent the particles from being broken by mechanical external forces during the process of taking the particles out of the granulator and putting them into a dryer or a heat treatment furnace. Therefore, after adding deionized water for granulation, an organic binder such as PVA is sprayed so that the organic binder is thinly covered on the surface of the powder to enhance the mechanical strength of the raw particles and complete the granulation. This method will inevitably lead to an increase in the carbon content of tantalum powder due to the introduction of organic matter during the agglomeration process, and the increase in the carbon content of tantalum powder will lead to an increase in the leakage current of tantalum electrolytic capacitors.
[0008] Japanese patent JP5183145B2 uses a granulator equipped with high-speed rotating stirring blades and crushing blades, and uses a granulator equipped with wings and a sprayer for spraying water into a container. It attempts a process of adding water to tantalum secondary particles while stirring to obtain a water-containing powder, and a process of stirring the water-containing powder without adding water to obtain a granulated powder, and obtains tantalum powder particles with a narrow particle size distribution.
[0009] U.S. Patent No. 9831041B2 proposes a method of obtaining granulated powder by combining a step of stirring while adding water with a subsequent step of stirring without adding water in a granulating device, crushing the tantalum powder obtained by sodium reduction, adding water thereto to obtain a hydrated aggregate, drying the hydrated aggregate to obtain a dry aggregate; sieving the dried aggregate to obtain rounded particles, and heat-treating the rounded particles. The invention provides a method for producing spherical tantalum agglomerated particles with a small and narrow particle size and low bulk density. In addition, it aims to provide a high surface area porous tantalum powder particle with large diameter voids.
[0010] Chinese patent CN1238251A discloses a method for obtaining agglomerated tantalum powder by granulating fine tantalum powder into granules on a granulation disk without adding any binder but only adding deionized water, then vibrating and sieving the granulated tantalum powder, and drying the granulated tantalum powder, vacuum heat-treating the granulated granules to generate sintering between the granulated granules, and crushing and sieving the loose porous body obtained after the heat treatment.
[0011] Chinese patent CN102806345A discloses a tantalum powder granulation device and a method for pelletizing tantalum powder using the device, wherein the granulation device is composed of a sieve, a fixed rotating frame rotating in a horizontal plane, and a receiving plate placed under the sieve. The present invention also discloses a method for granulating and manufacturing agglomerated tantalum powder, wherein the tantalum powder is mixed with a liquid to form a wet tantalum powder with a porosity of more than 40%, and then granulation is performed to form a separable agglomerated wet tantalum powder with a porosity of at least 30%, and the separable agglomerated wet tantalum powder is dried to obtain a pre-agglomerated tantalum powder granulation body, and then the pre-agglomerated tantalum powder granulation body is heat-treated and crushed to obtain agglomerated tantalum powder.
[0012] Chinese patent CN117733137A provides a method for preparing agglomerated tantalum powder, which comprises adding a volatile liquid to the raw tantalum powder in a spraying manner, mechanically mixing the volatile liquid and the raw tantalum powder to obtain a wet material, and then granulating the wet material using a rotary vibrating screen. This method can make the volatile liquid evenly distributed in the raw tantalum powder, thereby improving the fluidity of the agglomerated tantalum powder. This method can reduce the amount of volatile liquid, make the volatile liquid in the wet material volatilize better, increase the porosity of the tantalum powder, and improve the fluidity of the agglomerated tantalum powder.
[0013] The tantalum powder pelletizing methods used in patents JP3105294B2, CN1238251A, and CN102806345A all involve adding a pelletizing agent to the tantalum powder once, followed by granulation and screening, vacuum drying, heat treatment, and crushing to obtain pelletized tantalum powder. This type of pelletizing process generally has the disadvantage of using a one-time addition of a pelletizing agent, which results in uneven distribution of the pelletizing agent in the tantalum powder. The purpose of adding a pelletizing agent is to utilize the interaction of capillary water on the surface of tantalum powder particles to generate surface tension between particles and bond them to each other. For tantalum powder containing a small amount of pelletizing agent, due to the small amount of pelletizing agent per unit weight (or unit volume or unit surface area), the bonding effect between tantalum powder particles is poor, and the proportion of fine powder obtained is relatively large; for tantalum powder containing a large amount of pelletizing agent, the bonding effect between tantalum powder particles is good, and the resulting coarse particles are more; therefore, the distribution of the pelletizing agent is uneven, which will cause uneven distribution of coarse and fine secondary particles of tantalum powder and a wide particle size distribution in the subsequent pelletizing process. The method and equipment used in patent JP5183145B2 are complex to operate. While using crushing blades to crush coarse secondary particles during the granulation process, there is a risk of destroying the microstructure of primary particles. Patent CN117733137A adopts a spraying method to add a pelletizing agent, and then uses a rotary vibrating screen to granulate the tantalum powder after it is moistened. Although this method improves the method of adding the pelletizing agent, it cannot effectively control the particle size distribution during the granulation process.
[0014] In summary, the tantalum powder pelletizing method used in the prior art lacks effective control, whether in terms of the addition method of the pelletizing agent or the adjustment of the coarse and fine tantalum powders during the granulation process. In the granulation process, the granulation time is directly proportional to the particle size of the tantalum powder particles, that is, the longer the granulation time, the larger the particle size of the tantalum powder particles. When the coarse and fine particles are pelletized for the same time, the particle size distribution of the pelletized tantalum powder will become more discrete due to the long granulation time, resulting in uneven particle size distribution of the tantalum powder secondary particles. Based on the above analysis, in order to obtain pelletized tantalum powder with a low fine powder rate and a narrow particle size distribution, it is necessary to seek a tantalum powder pelletizing process with a high balling rate and uniform distribution of coarse and fine powders. Summary of the invention
[0015] In order to solve the above technical problems, the present invention provides a pelletizing device for improving the performance of tantalum powder and its application.
[0016] The present invention is achieved through the following technical solutions.
[0017] The present invention provides a pelletizing device for improving the performance of tantalum powder, which comprises a spraying device and a granulating device, wherein the discharge port of the spraying device is located above the granulating device.
[0018] Preferably, the spray device includes an air intake pipe, an air purifier, a flow regulating valve, an atomizing pipe, a storage tank and an atomizing nozzle. The air intake pipe is connected to one end of the atomizing pipe, and the other end of the atomizing pipe is connected to the atomizing nozzle. The air purifier, the flow regulating valve and the storage tank are sequentially arranged on the atomizing pipe from the air intake end to the air outlet end.
[0019] Preferably, the air intake pipe is connected to a compressed air generating device, the compressed air pressure is 0.6-0.8MPa, the air purifier is filled with an air filter, the atomizer nozzle is a wide-angle circular atomizing nozzle, the flow rate in the atomizing pipe is 20-60mL / min, and the spray pressure of the atomizer nozzle is 0.4-0.8MPa.
[0020] Preferably, the granulating device comprises a granulating body, a vibration motor and a base, the bottom of the granulating body is connected to the base, the vibration motor is arranged in the granulating body, and a storage barrel is arranged on the granulating body.
[0021] Preferably, an eccentric shaft A and an eccentric shaft B are arranged on the driving shaft of the vibration motor, and the eccentric shaft A and the eccentric shaft B are located below the storage barrel. The storage barrel is made of stainless steel, and an opening is arranged on the top of the storage barrel.
[0022] A method for using a pelletizing device for improving the performance of tantalum powder comprises the following steps:
[0023] 1) Load the tantalum powder raw material into the granulating device, load the pelletizing agent into the storage device of the spraying device, and start the granulating device and the spraying device at the same time to spray the pelletizing agent for the first time and granulate;
[0024] 2) sieving the wet tantalum powder obtained in step 1), and pouring out the powder on the sieve for later use;
[0025] 3) the undersize powder obtained in step 2) is loaded into a granulating device, the spheroidizing agent is loaded into a storage container of a spraying device, and the granulating device and the spraying device are started at the same time, and the spheroidizing agent is added by spraying for the second time and granulating;
[0026] 4) sieving the wet tantalum powder obtained in step 3), and pouring out the sieved powder for later use;
[0027] 5) The second undersize powder obtained in step 4) is loaded into a granulating device, and the spheroidizing agent is loaded into a spraying device, and the granulating device and the spraying device are started at the same time, and the spheroidizing agent is added by spraying for the third time and granulating;
[0028] 6) sieving the wet tantalum powder obtained in step 5), and pouring out the sieved powder for later use;
[0029] 7) pouring the oversize powder 1 obtained in step 2), the oversize powder 2 obtained in step 4), the oversize powder 3 obtained in step 6) and the undersize powder 3 obtained in step 6) into a granulating device for mixing;
[0030] 8) Screening the wet tantalum powder after mixing in step 7), and drying after all the powder is screened;
[0031] 9) The dried tantalum powder is subjected to heat treatment, and after the heat treatment, the tantalum powder is crushed and sieved to obtain pelletized tantalum powder.
[0032] Preferably, the tantalum powder raw material in step 1) is in ppm, and the chemical impurity content in the tantalum powder raw material includes: O≤4500, N≤100, C≤20, Fe≤20, Ni≤15, Cr≤15; the physical property index level of the tantalum powder raw material: the bulk density is 0.8-1.5g / cm 3 ; The average particle size of Fisher is 0.8-1.5μm;
[0033] The pelletizing agent includes deionized water or deionized water containing any one or more of the dopants NH4H2PO4, (NH4)2HPO4, H3PO4, and NH4PF6;
[0034] In the step 1), the charging ratio of tantalum powder to pelletizing agent is 0-20 ml / kg;
[0035] In the step 3), the charging ratio of tantalum powder to pelletizing agent is 0-15 ml / kg;
[0036] In the step 5), the charging ratio of tantalum powder to pelletizing agent is 0-10 ml / kg.
[0037] Preferably, in the steps 1), 3) and 5), the amount of water sprayed by the spray device is 2-10% of the weight of the tantalum powder, and the granulation time of the granulation device is 1-15 minutes;
[0038] The vibrating screening equipment in steps 2), 4) and 6) is a rotary vibrating screen, the vibration frequency of the rotary vibrating screen is 1200-1600r / min, and the mesh size is 50 or 60 mesh; the vibrating screening equipment in step 7) is a rotary vibrating screen, the vibration frequency of the rotary vibrating screen is 1200-1600r / min, and the mesh size is 40 or 50 mesh; the drying temperature in step 8) is 100-150°C, the drying time is 8-15h, and the drying temperature is 1×10 -1 Pa-1×10 2 The deionized water in the tantalum powder is removed under a pressure of Pa; the heat treatment in step 9) is carried out under a vacuum degree of less than 5×10 -3The heat treatment is carried out under a vacuum degree of Pa, and the temperature is 1000-1600°C for 60-180min. The heat treatment can be divided into three stages: firstly heating to 600-800°C, keeping warm for 30-120min, then heating to 1000-1200°C, keeping warm for 30-120min, and then heating to 1400-1600°C for 30-120min.
[0039] The tantalum powder prepared by the pelletizing device for improving the performance of tantalum powder has a specific volume between 8000uF·V / g and 20000uF·V / g.
[0040] A tantalum anode or capacitor prepared by using the above tantalum powder.
[0041] The beneficial effects of the present invention are:
[0042] Compared with the prior art, the present invention changes the way the pelletizing agent is added. Through the pelletizing method of multiple spraying, multiple granulation, and multiple screening, the uneven distribution of secondary particles and excessive agglomeration of secondary particles caused by uneven addition of the pelletizing agent and long granulation time of the tantalum powder are avoided. The low porosity and large capacity loss caused by adding too much pelletizing agent at one time are avoided. The uniformity of the secondary particle size is improved, the proportion of -400 mesh tantalum powder fines is reduced, the loose packing density of tantalum powder is increased, the breakdown voltage of tantalum electrolytic capacitors is increased, and the leakage current of tantalum electrolytic capacitors is reduced. The tantalum powder prepared by the pelletizing method has uniform particle size and low fine powder rate, so that the tantalum electrolytic capacitors prepared thereby have low leakage current, good voltage resistance, and high reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is a pelletizing operation flow chart of an embodiment of the present invention;
[0044] Figure 2 is a schematic diagram of a tantalum powder spraying device and a granulating device of the present invention;
[0045] Figure 3 , Figure 4 is a scanning electron microscope photograph of Example 3 of the present invention after pelletization;
[0046] In the figure: 1-intake pipe, 2-flow regulating valve, 3-atomizing pipe, 4-storage device, 5-atomizer nozzle, 6-tantalum powder material, 7-granulating body, 71-placing cylinder, 8-eccentric shaft A, 9-vibration motor, 10-base, 11-eccentric shaft B, 12-air purifier. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described below, but the scope of protection claimed is not limited to the description.
[0048] like Figure 1As shown, a pelletizing device for improving the performance of tantalum powder includes a spray device and a granulating device, wherein the discharge port of the spray device is located above the granulating device.
[0049] The spray device comprises an air intake pipe 1, an air purifier 12, a flow regulating valve 2, an atomizing pipe 3, a storage container 4 and an atomizing nozzle 5. The air intake pipe 1 is connected to one end of the atomizing pipe 3, and the other end of the atomizing pipe 3 is connected to the atomizing nozzle 5. The atomizing pipe 3 is provided with an air purifier 12, a flow regulating valve 2 and a storage container 4 in sequence from the air intake end to the air outlet end. The air intake pressure of the compressed air is adjusted by the flow regulating valve 2, so as to control the spray volume; the storage container 4 is used for storing the pelletizing agent, and its volume is 5-8L.
[0050] The air intake pipe 1 is connected to a compressed air generating device, and the compressed air pressure is 0.6-0.8MPa. The air purifier 12 is filled with an air filter to filter particulate matter in the air; the atomizer nozzle 5 is a wide-angle circular atomizing nozzle, and the nozzle aperture is 0.5mm. The flow rate in the atomizing pipe 3 is 20-60mL / min, and the spray pressure of the atomizer nozzle 5 is 0.4-0.8MPa. The compressed air and the atomizer nozzle 5 are atomized into ultra-fine water mist and then sprayed out. After the spray device is started, the spray can be evenly sprayed on the surface of the material in the storage tube 71.
[0051] The spray formation process is that the compressed air passes through the air purifier 12 and enters the atomizing pipe 3 through the air intake pipe 1. The flow regulating valve 2 adjusts the compressed air pressure. The pelletizing agent in the storage container 4 is mixed with the compressed air in the atomizer nozzle 5 due to the siphon effect and then sprayed out to produce fine atomized spray.
[0052] The granulating device comprises a granulating body 7, a vibration motor 9 and a base 10. The bottom of the granulating body 7 is connected to the base 10. The vibration motor 9 is arranged in the granulating body 7. A storage tube 71 is arranged on the granulating body 7. The diameter of the granulating body 7 can be 400-800mm, and different sizes can be set according to actual needs.
[0053] The driving shaft of the vibration motor 9 is provided with an eccentric shaft A8 and an eccentric shaft B11, and the eccentric shaft A8 and the eccentric shaft B11 are located below the storage barrel 71. The storage barrel 71 and the base 10 are made of stainless steel, and an opening is provided at the top of the storage barrel 71. The storage barrel 71 is driven by the vibration motor 9 to rotate the eccentric shaft A8 and the eccentric shaft B11, so that the storage barrel 71 rotates in the horizontal plane.
[0054] The main shaft of the vibration motor 9 simultaneously drives the eccentric shaft A8 and the eccentric shaft B11 to rotate and perform eccentric motion. Under the action of the eccentric shaft A8 and the eccentric shaft B11, the particles of the tantalum powder material 6 in the bottom of the storage barrel 71 perform eccentric motion along the movement direction of the main shaft of the vibration motor 9. The tantalum powder material 6 performs circular motion in the storage barrel 71 under the action of the centripetal force. During the motion, the tantalum powder particles gather into spherical particles with larger size in a manner similar to snowballing. Normally, after the pelletizing agent is loaded into the storage container 4 and the tantalum powder to be pelletized is loaded into the storage barrel 71 of the granulator body 7, the vibration motor 9 is started first, and then the spray device is started and the flow regulating valve 2 is opened for spraying.
[0055] A method for using a pelletizing device for improving the performance of tantalum powder comprises the following steps:
[0056] 1) Loading the tantalum powder raw material into the granulating device, loading the pelletizing agent into the storage container 4 of the spraying device, and simultaneously starting the granulating device and the spraying device to spray the pelletizing agent for the first time and granulate;
[0057] 2) sieving the wet tantalum powder obtained in step 1), and pouring out the powder on the sieve for later use;
[0058] 3) The undersize powder obtained in step 2) is loaded into a granulating device, and the spheroidizing agent is loaded into a storage container 4 of a spraying device, and the granulating device and the spraying device are started at the same time to spray and add the spheroidizing agent for the second time and granulate;
[0059] 4) sieving the wet tantalum powder obtained in step 3), and pouring out the sieved powder for later use;
[0060] 5) The second undersize powder obtained in step 4) is loaded into a granulating device, and the spheroidizing agent is loaded into a spraying device, and the granulating device and the spraying device are started at the same time, and the spheroidizing agent is added by spraying for the third time and granulating;
[0061] 6) sieving the wet tantalum powder obtained in step 5), and pouring out the sieved powder for later use;
[0062] 7) pouring the oversize powder 1 obtained in step 2), the oversize powder 2 obtained in step 4), the oversize powder 3 obtained in step 6) and the undersize powder 3 obtained in step 6) into a granulating device for mixing;
[0063] 8) Screening the wet tantalum powder after mixing in step 7), and drying after all the powder is screened;
[0064] 9) The dried tantalum powder is heat treated, and after the heat treatment, the tantalum powder is crushed and sieved to obtain pelletized tantalum powder. The pelletized tantalum powder is subjected to heat treatment, deoxidation and acid washing to obtain the prepared capacitor-grade tantalum powder. The relevant process of step 9) can be the existing technology, and the process can be adjusted according to the needs of the capacitor.
[0065] The tantalum powder raw material in step 1) is tantalum powder that has been ball-milled, acid-washed, and once heat-treated. The above-mentioned related processes can be existing technologies and can be adjusted according to the needs of capacitors. In units of ppm, the chemical impurity content in the tantalum powder raw material includes: O≤4500, N≤100, C≤20, Fe≤20, Ni≤15, Cr≤15; the physical property index level of the tantalum powder raw material: the bulk density is 0.8-1.5g / cm 3 ; The average particle size of Fisher is 0.8-1.5μm;
[0066] The pelletizing agent includes deionized water or deionized water containing any one or more of dopants NH4H2PO4, (NH4)2HPO4, H3PO4, and NH4PF6. The purpose of adding the dopant is to improve the sintering resistance of the tantalum powder particles and reduce the capacity loss during the heat treatment process.
[0067] In the step 1), the charging ratio of tantalum powder to pelletizing agent is 0-20 ml / kg;
[0068] In the step 3), the charging ratio of tantalum powder to pelletizing agent is 0-15 ml / kg;
[0069] In the step 5), the charging ratio of tantalum powder to pelletizing agent is 0-10 ml / kg.
[0070] In the steps 1), 3) and 5), the water spraying amount of the spraying device is 2-10% of the weight of the tantalum powder, and the granulation time of the granulation device is 1-15 minutes;
[0071] The vibrating screening equipment described in steps 2), 4) and 6) is a rotary vibrating screen, the vibration frequency of the rotary vibrating screen is 1200-1600r / min, and the mesh size is 50 or 60 mesh; the vibrating screening equipment described in step 8) is a rotary vibrating screen, the vibration frequency of the rotary vibrating screen is 1200-1600r / min, and the mesh size is 40 or 50 mesh; the drying temperature in step 8) is 100-150°C, the drying time is 8-15h, and the drying temperature is 1×10 -1 Pa-1×10 2 Pa to remove the deionized water in the tantalum powder, and the heat treatment in step 9) is carried out at a vacuum degree of less than 5×10 -3 The heat treatment is carried out under a vacuum degree of Pa, and the temperature is 1000-1600°C for 60-180min. The heat treatment can be divided into three stages: firstly heating to 600-800°C, keeping warm for 30-120min, then heating to 1000-1200°C, keeping warm for 30-120min, and then heating to 1400-1600°C for 30-120min.
[0072] The detection methods of elements in tantalum powder of the present invention are all derived from national standards such as GB / T 15076.8-2008, GB / T 15076.9-2008, GB / T 15076.12-2008, GB / T 15076.14-2008, GB / T15076.15-2008, GB / T 15076.16-2008 and "Chemical Analysis Methods for Tantalum and Niobium".
[0073] The Fischer-Strauss particle size (FSSS / μm) of the tantalum powder of the present invention is measured according to the method specified in the standard "Fischer-Strauss method for determination of particle size of refractory metal and compound powders" (standard number GB / T3249); the bulk density (SBD) is measured according to the method specified in the standard "Determination of bulk density of metal powders - Part 1 - Funnel method" (standard number GB / T1479); the particle size distribution is measured according to the method specified in the standard "Determination of particle size composition of metal powders - Dry sieving method" (standard number GB / T1480); the fluidity is measured by referring to the method specified in the national standard "Determination of bulk density of metal powders - Part 1 - Funnel method" (standard number GB 1482-84); and the sampling process is sampled according to the method specified in the technical standard "Sampling method for powder metallurgy" (standard number GB / T5314).
[0074] The detection methods of elements in tantalum powder in the present invention are all determined in accordance with national standards, including "GB / T15076.8-2008 Chemical analysis method for tantalum and niobium for determination of carbon and sulfur content", "GB / T15076.9-2008 Chemical analysis method for tantalum and niobium for determination of iron, chromium, nickel, manganese, titanium, aluminum, copper, tin, lead and tantalum in tantalum", "GB / T15076.12-2008 Chemical analysis method for tantalum and niobium for determination of phosphorus content in tantalum", "GB / T15076.14-2008 Chemical analysis method for tantalum and niobium for determination of oxygen content", "GB / T15076.15-2008 Chemical analysis method for tantalum and niobium for determination of hydrogen content",
[0075] GB / T15076.16-2008 Chemical analysis method for tantalum and niobium - Determination of sodium and potassium content.
[0076] The detection methods and equipment for the electrical properties of tantalum powder in the present invention all refer to national standards.
[0077] Determined according to GB / T3137-2007 Test method for electrical properties of tantalum powder.
[0078] Embodiment 1:
[0079] Weigh 2kg of raw tantalum powder and load it into the granulation device. In units of ppm, the chemical impurity content in the raw tantalum powder is: O=4257, N=68, C=19, Fe=20, Ni=7, Cr=13; the physical property index level of the raw tantalum powder is: the bulk density is 0.8g / cm 3; The average particle size of Fisher is 1.2μm;
[0080] 400 ml of a pelletizing agent (20% of the weight of the tantalum powder) was measured and poured into a sprayer. The pelletizing agent was deionized water containing a dopant NH4PF6, and the doping amount of the dopant (calculated in terms of P element content) was 60 ppm.
[0081] After loading is completed, the granulation device and the sprayer are started at the same time, so that the tantalum powder is mixed in the granulation device, and the spheroidizing agent sprayed by the sprayer is evenly sprayed on the surface of the tantalum powder. The compressed air pressure is 0.8MPa; by adjusting the flow regulating valve 2, the flow rate in the atomization tube 3 is adjusted to 30mL / min, the spray pressure of the atomizer nozzle 5 is 0.5MPa, the granulation time is 20min, the spray time is 15min, and the granulation device continues to granulate for 5min after the spraying is completed. After the granulation is completed, the tantalum powder in the granulation device is shoveled into the rotary vibrating screen for screening. The mesh of the rotary vibrating screen is 50 mesh. When all the tantalum powder in the rotary vibrating screen has been screened, the rotary vibrating screen is closed.
[0082] The pelletized tantalum powder is subjected to vacuum drying, heat treatment, oxygen reduction and other subsequent treatment steps to obtain the pelletized tantalum powder product. The vibration frequency of the rotary vibrating screen is 1200r / min, the drying temperature is 100℃, the drying time is 10h, and the temperature is 1×10 -1 Pa to remove the deionized water in the tantalum powder, and the heat treatment in step 9) is carried out at a vacuum degree of less than 5×10 -3 The heat treatment is carried out under a vacuum degree of Pa and at 1400°C, wherein the heat treatment is divided into three stages of heating: firstly heating to 600°C and keeping it warm for 30 min, then heating to 1000°C and keeping it warm for 60 min, and then heating to 1400°C and keeping it warm for 60 min.
[0083] The obtained tantalum powder was tested for bulk density, sieve analysis, fluidity, and average particle size. The results are listed in Table 1.
[0084] Embodiment 2:
[0085] Weigh 2kg of raw tantalum powder and put it into the granulation device. The chemical impurity content in the raw tantalum powder is in ppm: O=4257, N=68, C=19, Fe=20, Ni=7, Cr=13; the physical property index level of the raw tantalum powder is: the bulk density is 0.8g / cm 3 ; The average particle size of Fisher is 1.2μm;
[0086] 200 ml of pelletizing agent (10% of the weight of tantalum powder) was measured and poured into the sprayer. After loading, the granulator and the sprayer were started at the same time, so that the tantalum powder was mixed in the granulator while the pelletizing agent sprayed from the sprayer was evenly sprayed on the surface of the tantalum powder. The compressed air pressure was 0.8 MPa. The flow rate in the atomizing tube 3 was adjusted to 25 mL / min by adjusting the flow regulating valve 2, the spray pressure of the atomizer nozzle 5 was 0.4 MPa, the powder mixing time was 10 min, the spraying time was 8 min, and the granulator continued to mix the powder for 2 min after the spraying was completed. After the powder mixing was completed, the tantalum powder in the granulator was shoveled into the rotary vibrating screen for screening. The mesh of the rotary vibrating screen was 60 mesh. After screening for 3 min, the powder on the screen was poured into a stainless steel plate.
[0087] The powder under the sieve is poured into the granulation device, 200 ml of the pelletizing agent (10% of the weight of the tantalum powder) is measured and poured into the sprayer, and the granulation device and the sprayer are started at the same time, and the compressed air pressure is 0.8 MPa; by adjusting the flow regulating valve 2, the flow rate in the atomization tube 3 is adjusted to 25 mL / min, the spray pressure of the atomizer nozzle 5 is 0.4 MPa, the powder mixing time is 10 min, and the spraying time is 8 min. After the spraying is completed, the granulation device is ensured to continue mixing the powder for 2 min. After the powder mixing is completed, the tantalum powder in the granulation device is shoveled into the rotary vibrating screen for screening. The mesh of the rotary vibrating screen is 60 mesh. After screening for 3 minutes, all the powder on the sieve in the stainless steel plate is poured into the granulation device, and the granulation device is started to mix the powder for 2 minutes, and the powder mixing is completed;
[0088] The tantalum powder in the granulation device is shoveled into the rotary vibrating screen for screening. The mesh of the rotary vibrating screen is 50 mesh. When all the tantalum powder in the rotary vibrating screen has been screened, the rotary vibrating screen is closed.
[0089] The pelletized tantalum powder is subjected to subsequent treatment steps such as vacuum drying, heat treatment, and oxygen reduction to obtain a pelletized tantalum powder product.
[0090] The pelletizing agent is deionized water containing dopant NH4PF6, and the doping amount of the dopant (calculated by P element content) is 60ppm;
[0091] The vibration frequency of the rotary vibrating screen is 1600r / min, the drying temperature is 150℃, the drying time is 8h, and the drying temperature is 1×10 2 The deionized water in the tantalum powder is removed under a pressure of Pa; the heat treatment in step 9) is carried out under a vacuum degree of less than 5×10 -3 The heat treatment is carried out under a vacuum degree of Pa and at 1400°C, wherein the heat treatment is divided into three stages of heating: firstly heating to 600°C and keeping it warm for 30 min, then heating to 1000°C and keeping it warm for 60 min, and then heating to 1400°C and keeping it warm for 60 min.
[0092] The obtained tantalum powder was tested for bulk density, sieve analysis, fluidity, and average particle size. The results are listed in Table 1.
[0093] Embodiment 3:
[0094] Weigh 2kg of raw tantalum powder and put it into the granulation device. The chemical impurity content in the raw tantalum powder is in ppm: O=4257, N=68, C=19, Fe=20, Ni=7, Cr=13; the physical property index level of the raw tantalum powder is: the bulk density is 0.8g / cm 3 ; The average particle size of Fisher is 1.2μm;
[0095] Use a measuring cylinder to measure 100 ml of pelletizing agent (5% of the weight of tantalum powder) and pour it into the spray device. After loading, the compressed air pressure is 0.8 MPa. By adjusting the flow regulating valve 2, the flow rate in the atomizing tube 3 is adjusted to 20 mL / min, and the spray pressure of the atomizer nozzle 5 is 0.4 MPa. At the same time, start the granulating device and the sprayer, so that while the tantalum powder is granulated in the granulating device, the pelletizing agent sprayed by the sprayer is evenly sprayed on the surface of the tantalum powder. The granulation time is 8 minutes, and the spray time is 6 minutes. After the spraying is completed, the spray valve is closed, and the granulating device continues to granulate for 2 minutes, and the granulation is completed;
[0096] Close the granulation device, shovel the tantalum powder in the granulation device into the rotary vibrating screen for screening, the mesh of the rotary vibrating screen is 60 mesh, after screening for 3 minutes, pour the powder on the screen into a stainless steel plate for standby, and pour the powder under the screen into the granulation device; measure 100ml of pelletizing agent (5% of the weight of tantalum powder) and pour it into the spray device, the compressed air pressure is 0.8MPa, by adjusting the flow regulating valve 2, adjust the flow rate in the atomizing pipe 3 to 25mL / min, the spray pressure of the atomizer nozzle 5 is 0.5MPa, start the granulation device and the sprayer at the same time, the granulation time is 6min, the spray time is 4min, after the spraying is completed, ensure that the granulation device continues to granulate for 1min, and the granulation is completed;
[0097] The tantalum powder in the granulation device is shoveled into a rotary vibrating screen for screening. The mesh of the rotary vibrating screen is 60 mesh. After screening for 3 minutes, the powder on the screen is poured into a stainless steel plate for standby use; the powder under the screen is poured into the granulation device, 100 ml of a pelletizing agent (5% of the weight of the tantalum powder) is measured and poured into the sprayer, the compressed air pressure is 0.8 MPa, and the flow rate in the atomization pipe 3 is adjusted to 35 mL / min by adjusting the flow regulating valve 2. The spray pressure of the atomizer nozzle 5 is 0.6 MPa, and the granulation device and the sprayer are started at the same time. The granulation time is 4 minutes, and the spray time is 3 minutes. After the spraying is completed, the granulation device is ensured to continue granulating for 1 minute, and the granulation is completed;
[0098] The tantalum powder in the granulating device is shoveled into the rotary vibrating sieve for screening. The mesh of the rotary vibrating sieve is 60 mesh. After screening for 3 minutes, the powder on the sieve is poured into the stainless steel plate, and the powder under the sieve is poured into the granulating device. 100 ml of pelletizing agent (5% of the weight of tantalum powder) is measured and poured into the sprayer. The compressed air pressure is 0.8 MPa. By adjusting the flow regulating valve 2, the flow rate in the atomizing tube 3 is adjusted to 50 mL / min. The spray pressure of the atomizer nozzle 5 is 0.8 MPa. The granulating device and the sprayer are started at the same time. The granulation time is 3 minutes and the spray time is 2 minutes. After the spraying is completed, the granulating device is ensured to continue granulating for 1 minute. After the granulation is completed, the granulating device is closed, and all the powder on the sieve in the stainless steel plate is poured into the granulating device. The granulating device is started to mix the powder for 2 minutes. After the powder mixing is completed, the tantalum powder in the granulating device is shoveled into the rotary vibrating sieve for screening. The mesh of the rotary vibrating sieve is 50 mesh. When all the tantalum powder in the rotary vibrating sieve is sieved, the rotary vibrating sieve is closed.
[0099] The pelletized tantalum powder is subjected to subsequent treatment steps such as vacuum drying, heat treatment, and oxygen reduction to obtain a pelletized tantalum powder product.
[0100] The pelletizing agent is deionized water containing dopant NH4PF6, and the doping amount of the dopant (calculated by P element content) is 60ppm;
[0101] The vibration frequency of the rotary vibrating screen is 1400r / min, the drying temperature is 130℃, the drying time is 10h, and the drying temperature is 1×10 1 removing deionized water from the tantalum powder at a pressure of Pa;
[0102] The heat treatment in step 9) is carried out at a vacuum degree of less than 5×10 -3 The heat treatment is carried out under a vacuum degree of Pa and at 1400°C. The heat treatment is divided into three stages: first heating to 600°C and keeping warm for 60 min, then heating to 1000°C and keeping warm for 60 min, and then heating to 1400°C and keeping warm for 60 min.
[0103] The obtained tantalum powder was tested for bulk density, sieve analysis, fluidity, and average particle size. The results are listed in Table 1.
[0104] Embodiment 4:
[0105] Weigh 2kg of raw tantalum powder and load it into the granulation device. In units of ppm, the chemical impurity content in the tantalum powder raw material is: O=4218, N=65, C=19, Fe=20, Ni=6, Cr=14; the physical property index level of tantalum powder raw material: bulk density is 0.98g / cm 3 ; The average particle size of Fisher is 1.2μm;
[0106] Use a measuring cylinder to measure 100 ml of pelletizing agent (5% of the weight of tantalum powder) and pour it into the spray device. After loading, start the granulating device and the sprayer at the same time, so that the tantalum powder is granulated in the granulating device, and the pelletizing agent sprayed by the sprayer is evenly sprayed on the surface of the tantalum powder. The compressed air pressure is 0.8 MPa. By adjusting the flow regulating valve 2, the flow rate in the atomizing pipe 3 is adjusted to 20 mL / min. The spray pressure of the atomizer nozzle 5 is 0.4 MPa. The granulation time is 8 minutes, and the spray time is 6 minutes. When the spraying is completed, the spray valve is closed, and the granulating device continues to granulate for 2 minutes, and the granulation is completed;
[0107] Close the granulation device, shovel the tantalum powder in the granulation device into the rotary vibrating screen for screening, the mesh of the rotary vibrating screen is 50 mesh, after screening for 3 minutes, pour the powder on the screen into a stainless steel plate for standby, and pour the powder under the screen into the granulation device; measure 100ml of pelletizing agent (5% of the weight of tantalum powder) and pour it into the spray device, the compressed air pressure is 0.8MPa, by adjusting the flow regulating valve 2, adjust the flow rate in the atomizing pipe 3 to 25mL / min, the spray pressure of the atomizer nozzle 5 is 0.5MPa, start the granulation device and the sprayer at the same time, the granulation time is 6min, the spray time is 4min, after the spraying is completed, ensure that the granulation device continues to granulate for 2min, and the granulation is completed;
[0108] The tantalum powder in the granulation device is shoveled into a rotary vibrating sieve for screening. The mesh of the rotary vibrating sieve is 50 mesh. After screening for 3 minutes, the powder on the sieve is poured into a stainless steel plate for standby use; the powder under the sieve is poured into the granulation device, and 100 ml of a pelletizing agent (5% of the weight of the tantalum powder) is measured and poured into the sprayer. The compressed air pressure is 0.8 MPa. By adjusting the flow regulating valve 2, the flow rate in the atomizing pipe 3 is adjusted to 35 mL / min. The spray pressure of the atomizer nozzle 5 is 0.6 MPa. The granulation device and the sprayer are started at the same time. The granulation time is 4 minutes, and the spray time is 3 minutes. After the spraying is completed, the granulation device is ensured to continue granulating for 1 minute, and the granulation is completed;
[0109] The tantalum powder in the granulating device is shoveled into the rotary vibrating sieve for screening. The mesh of the rotary vibrating sieve is 50 mesh. After screening for 3 minutes, the powder on the sieve is poured into the stainless steel plate, and the powder under the sieve is poured into the granulating device. 100 ml of pelletizing agent (5% of the weight of tantalum powder) is measured and poured into the sprayer. The compressed air pressure is 0.8 MPa. By adjusting the flow regulating valve 2, the flow rate in the atomizing tube 3 is adjusted to 50 mL / min. The spray pressure of the atomizer nozzle 5 is 0.8 MPa. The granulating device and the sprayer are started at the same time. The granulation time is 3 minutes and the spray time is 2 minutes. After the spraying is completed, the granulating device is ensured to continue granulating for 1 minute. After the granulation is completed, the granulating device is closed, and all the powder on the sieve in the stainless steel plate is poured into the granulating device. The granulating device is started to mix the powder for 2 minutes. After the powder mixing is completed, the tantalum powder in the granulating device is shoveled into the rotary vibrating sieve for screening. The mesh of the rotary vibrating sieve is 40 mesh. When all the tantalum powder in the rotary vibrating sieve is sieved, the rotary vibrating sieve is closed.
[0110] The pelletized tantalum powder is subjected to subsequent treatment steps such as vacuum drying, heat treatment, and oxygen reduction to obtain a pelletized tantalum powder product.
[0111] The pelletizing agent is deionized water containing a dopant NH4H2PO4, and the doping amount of the dopant (calculated by the P element content) is 40ppm;
[0112] The vibration frequency of the rotary vibrating screen is 1400r / min, the drying temperature is 130℃, the drying time is 10h, and the drying temperature is 1×10 1 The deionized water in the tantalum powder is removed under a pressure of Pa; the heat treatment in step 9) is carried out under a vacuum degree of less than 5×10 -3 The heat treatment is carried out under a vacuum degree of Pa and at 1480°C. The heat treatment can be divided into three stages: first heating to 600°C, keeping warm for 60 minutes, then heating to 1250°C, keeping warm for 60 minutes, and then heating to 1480°C and keeping warm for 60 minutes.
[0113] The obtained tantalum powder was tested for bulk density, sieve analysis, fluidity, and average particle size. The results are listed in Table 1.
[0114] Comparative Example 1:
[0115] Weigh 2kg of raw tantalum powder and put it into the granulation device. The chemical impurity content in the raw tantalum powder is in ppm: O=4257, N=68, C=19, Fe=20, Ni=7, Cr=13; the physical property index level of the raw tantalum powder is: the bulk density is 0.8g / cm 3; The Fisher average particle size is 1.2μm; 160ml of pelletizing agent (8% of the weight of tantalum powder) is measured and poured into the tantalum powder for wetting, and the tantalum powder is mixed with a stainless steel shovel, and the wet tantalum powder is shoveled into the granulation device, and 100ml of pelletizing agent (5% of the weight of tantalum powder) is measured and poured into the sprayer, and the granulation device is started to mix the powder for 2 minutes, and then the sprayer is started. The compressed air pressure is 0.8MPa, and the flow rate in the atomization tube 3 is adjusted to 25mL / min by adjusting the flow regulating valve 2, and the spray pressure of the atomizer nozzle 5 is 0.5MPa. While the tantalum powder is granulated in the granulation device, the pelletizing agent sprayed by the sprayer is evenly sprayed on the surface of the tantalum powder. The granulation time is 8min, and the spraying time is 4min. After the spraying is completed, it is necessary to ensure that the granulation device continues to mix the powder for 4min, and the granulation is completed;
[0116] The tantalum powder in the granulation device is shoveled into the rotary vibrating screen for screening. The mesh of the rotary vibrating screen is 50 mesh. After screening for 5 minutes, the powder on the screen is poured into a stainless steel plate; the powder under the screen is poured into the granulation device, and 60 ml of a pelletizing agent (3% of the weight of the tantalum powder) is measured and poured into the sprayer. The compressed air pressure is 0.8 MPa. By adjusting the flow regulating valve 2, the flow rate in the atomizing pipe 3 is adjusted to 30 mL / min, and the spray pressure of the atomizer nozzle 5 is 0.5 MPa. The granulation device and the sprayer are started at the same time. The granulation time is 5 minutes, and the spray time is 2 minutes. After the spraying is completed, the granulation device is ensured to continue granulating for 3 minutes, and the granulation is completed;
[0117] The tantalum powder in the granulation device is shoveled into the rotary vibrating screen for screening. The mesh of the rotary vibrating screen is 50 mesh. After screening for 5 minutes, the powder on the screen is poured into a stainless steel plate; the powder under the screen is poured into the granulation device, and 40ml of the pelletizing agent (2% of the weight of the tantalum powder) is measured and poured into the sprayer. The compressed air pressure is 0.8MPa. By adjusting the flow regulating valve 2, the flow rate in the atomizing pipe 3 is adjusted to 20mL / min, and the spray pressure of the atomizer nozzle 5 is 0.4MPa. The granulation device and the sprayer are started at the same time. The granulation time is 5min, and the spray time is 2min. After the spraying is completed, the granulation device is ensured to continue granulating for 3min, and the granulation is completed;
[0118] The tantalum powder in the granulating device is shoveled into the rotary vibrating sieve for screening. The mesh of the rotary vibrating sieve is 50 mesh. After screening for 5 minutes, the powder on the sieve is poured into the stainless steel plate, and the powder under the sieve is poured into the granulating device. 40 ml of pelletizing agent (2% of the weight of tantalum powder) is measured and poured into the sprayer. The compressed air pressure is 0.8 MPa. By adjusting the flow regulating valve 2, the flow rate in the atomizing tube 3 is adjusted to 20 mL / min. The spray pressure of the atomizer nozzle 5 is 0.4 MPa. The granulating device and the sprayer are started at the same time. The granulation time is 5 minutes and the spray time is 2 minutes. After the spraying is completed, the granulating device is ensured to continue granulating for 3 minutes. After the granulation is completed, the granulating device is closed, and all the powder on the sieve in the stainless steel plate is poured into the granulating device. The granulating device is started to mix the powder for 2 minutes. After the mixing of powders is completed, the tantalum powder in the granulating device is shoveled into the rotary vibrating sieve for screening. The mesh of the rotary vibrating sieve is 50 mesh. When all the tantalum powder in the rotary vibrating sieve is sieved, the rotary vibrating sieve is closed.
[0119] The pelletized tantalum powder is subjected to vacuum drying, heat treatment, oxygen reduction and other subsequent treatment steps to obtain a pelletized tantalum powder product. The obtained tantalum powder is tested for bulk density, sieve analysis, fluidity and average particle size, and the results are listed in Table 1.
[0120] Comparative Example 2:
[0121] Weigh 2kg of raw tantalum powder and place it on a stainless steel plate. Weigh 2kg of raw tantalum powder and load it into the granulation device. In units of ppm, the chemical impurity content in the tantalum powder raw material is: O=4257, N=68, C=19, Fe=20, Ni=7, Cr=13; the physical property index level of tantalum powder raw material: loose density is 0.8g / cm 3 ; The Fisher average particle size is 1.2μm; 400ml of pelletizing agent (20% of the weight of tantalum powder) is poured into the tantalum powder for wetting, and the tantalum powder is mixed with a stainless steel shovel, and the wet tantalum powder is shoveled into the granulation device, and the granulation device is started to granulate for 8 minutes. After the granulation is completed, the tantalum powder in the granulation device is shoveled into the rotary vibrating screen for screening. The mesh of the rotary vibrating screen is 50 mesh. When all the tantalum powder in the rotary vibrating screen has been sieved, the rotary vibrating screen is closed.
[0122] The pelletized tantalum powder is subjected to vacuum drying, heat treatment, oxygen reduction and other subsequent treatment steps to obtain a pelletized tantalum powder product. The obtained tantalum powder is tested for bulk density, sieve analysis, fluidity and average particle size, and the results are listed in Table 1.
[0123] Comparative Example 3:
[0124] Weigh 2kg of raw tantalum powder and load it into the granulation device. In units of ppm, the chemical impurity content in the tantalum powder raw material is: O=4218, N=65, C=19, Fe=20, Ni=6, Cr=14; the physical property index level of tantalum powder raw material: bulk density is 0.98g / cm 3; The Fisher average particle size is 1.2μm; 400ml of pelletizing agent (20% of the weight of tantalum powder) is measured and poured into the tantalum powder for wetting. After mixing the tantalum powder with a stainless steel shovel, the wet tantalum powder is shoveled into the granulation device, and the granulation device is started to granulate for 10 minutes. After the granulation is completed, the tantalum powder in the granulation device is shoveled into the rotary vibrating screen for screening. The mesh of the rotary vibrating screen is 40 mesh. When all the tantalum powder in the rotary vibrating screen has been sieved, the rotary vibrating screen is closed.
[0125] The pelletized tantalum powder is subjected to subsequent treatment steps such as vacuum drying, heat treatment, and oxygen reduction to obtain a pelletized tantalum powder product.
[0126] The pelletizing agent is deionized water containing a dopant NH4H2PO4, and the doping amount of the dopant (calculated by the P element content) is 40ppm;
[0127] The obtained tantalum powder was tested for bulk density, sieve analysis, fluidity, and average particle size, and the results are listed in Table 1. The 7 samples obtained from Examples 1-4 and Comparative Examples 1-3 were analyzed, and the performance comparison results are shown in Table 1 below.
[0128] Table 1: Element content in tantalum powder (unit: ppm)
[0129]
[0130]
[0131] It can be seen from Table 1 that the chemical impurities in Examples 1-4 and Comparative Examples 1-3 did not undergo significant changes due to the different pelletizing processes, because the pelletizing process only involves changes in physical properties and has no effect on chemical properties.
[0132] Table 2: Physical properties of tantalum powder
[0133]
[0134] In Table 2:
[0135] FSSS stands for the Fisher Size System of the tantalum powder particles.
[0136] SBD stands for the apparent density of powders, which refers to the bulk density of powders measured after they are freely filled in a standard container under specified conditions, that is, the mass per unit volume of powders when loosely filled, in g / cm 3 It is a physical property of powder. The measurement method used here is the funnel method, that is, the powder falls freely from the funnel hole at a certain height and fills the cup.
[0137] Fluidity represents the flow effect of tantalum powder particles. It refers to the time required for 50g of powder to flow completely from the Hall flow meter under specified conditions. It is a property that characterizes the powder during the pressing process.
[0138] +80(%) indicates the proportion of particles larger than 80 mesh to all particles, -80(%) to +200(%) indicates the proportion of particles smaller than 80 mesh and particles larger than 200 mesh to all particles, -400(%) indicates the proportion of particles smaller than 400 mesh to all particles. Mesh refers to the number of meshes per inch (25.4mm) of the screen.
[0139] It can be seen from Table 2 that in Examples 1-4, with the increase of the number of spraying times, granulation times and screening times, the proportion of -80 to +325 mesh particles in all particles increases, indicating that the particle size distribution is more concentrated and narrower, and the proportion of +80 mesh coarse particles and -400 mesh fine particles of tantalum powder is significantly reduced; Comparative Examples 1-3 use the traditional pelletizing method for pelletizing. It can be seen from the table that the proportion of -400 mesh fine particles of tantalum powder is relatively large, and the pelletizing effect is not good.
[0140]
[0141] Table 3: Comparison of electrical properties (sintering conditions of Examples 1-3 and Comparative Examples 1-2: 1650°C / 30min, V f :160V, D 压 :5.0g / cm 3 ; Sintering conditions of Example 4 and Comparative Example 3: 1700°C / 30min, V f :160V, D 压 :5.5g / cm 3 )
[0142] In Table 3:
[0143] Sintering conditions: 1650°C / 30min means that tantalum powder is sintered at 1650°C for 30 minutes to obtain an anode block.
[0144] V f :160V means energizing at a voltage of 160V.
[0145] D 压 :5.0g / cm 3 Indicates that the pressed density of the anode block is 5.0g / cm 3 .
[0146] K×10 -4(μA / μF·V) represents leakage current, hereinafter referred to as K value. Since the capacitor medium cannot be absolutely non-conductive, when a DC voltage is applied to the capacitor, a leakage current will be generated in the capacitor. If the leakage current is too large, the capacitor will heat up and be damaged. When the rated DC working voltage is applied to the capacitor, it will be observed that the change in charging current is large at the beginning, and then decreases over time, reaching a relatively stable state at a certain final value. This final value current is called leakage current.
[0147] CV (μF·V / g) stands for specific capacity, which is the amount of electricity that can be discharged per unit weight of the battery or active material.
[0148] tgδ(%) represents the loss of the capacitor. The loss of the capacitor is actually the reactive power consumed by the capacitor, so it can also be defined as follows: The loss of the capacitor also refers to the ratio of the reactive power consumed by the capacitor under the action of the electric field to the total power consumed. The expression is: Capacitor loss angle tangent value = reactive power ÷ total power, or capacitor loss angle tangent value = reactive power ÷ total power (the value obtained is a percentage).
[0149] SHV (%) represents the volume shrinkage of the capacitor anode block.
[0150] The data in the above table (see Table 3) show that the specifications of Examples 1-3 and Comparative Examples 1-2 are 35V-15000uF·V / g tantalum powder, and the specifications of Example 4 and Comparative Example 3 are 35V-10000uF·V / g tantalum powder. It can be seen from the data of the embodiments and comparative examples of tantalum powder of two specifications that by using the pelletizing device of the present invention and adopting a pelletizing method of multiple spraying, multiple granulation and multiple screening, the particle size distribution of the particles is more concentrated and the particle size distribution is narrower. The proportion of +80 mesh coarse particles and -400 mesh fine particles of tantalum powder is significantly reduced, which is manifested in a slightly reduced specific capacity, a higher breakdown voltage, and lower leakage current and loss in terms of electrical performance.
[0151] On the other hand, if the fine powder ratio is high, there will be problems of excessive leakage current (K value) and loss (tgδ%), which is not preferred.
[0152] Therefore, for the tantalum powder with specifications of 35V-10000uF·V / g and 35V-15000uF·V / g of the present invention, when the -400 mesh fine tantalum powder is controlled below 10%, the breakdown voltage of the sample is higher, the leakage current is lower, and the electrical properties of the tantalum powder are better.
[0153] The present invention discloses a pelletizing device for improving the performance of tantalum powder, the device is composed of a spraying device and a granulating device, the spraying device is located directly above the granulating device, and can spray a spheroidizing agent more evenly on the surface of the material while the granulating device is granulating. The present invention also discloses a tantalum powder spheroidizing method, the spheroidizing method changes the incorporation mode of the spheroidizing agent, and uses a spheroidizing method of multiple spraying, multiple granulation, and multiple screening to avoid the uneven distribution of secondary particles and excessive agglomeration of secondary particles caused by uneven addition of the spheroidizing agent and long granulation time, improves the uniformity of the secondary particle size, and reduces the proportion of -400 mesh tantalum fine powder.
Claims
1. A pelletizing device for improving the performance of tantalum powder, characterized in that: It comprises a spray device and a granulating device, wherein the discharge port of the spray device is located above the granulating device.
2. A pelletizing device for improving the performance of tantalum powder as claimed in claim 1, characterized in that: The spray device comprises an air intake pipe (1), an air purifier (12), a flow regulating valve (2), an atomizing pipe (3), a accumulator (4) and an atomizing nozzle (5); the air intake pipe (1) is connected to one end of the atomizing pipe (3), the other end of the atomizing pipe (3) is connected to the atomizing nozzle (5), and the air purifier (12), the flow regulating valve (2) and the accumulator (4) are arranged on the atomizing pipe (3) in sequence from the air intake end to the air outlet end.
3. A pelletizing device for improving the performance of tantalum powder as claimed in claim 2, characterized in that: The air intake pipe (1) is connected to a compressed air generating device, and the compressed air pressure is 0.6-0.8 MPa; the air purifier (12) is filled with an air filter, the atomizer nozzle (5) is a wide-angle circular atomizing nozzle, the flow rate in the atomizing pipe (3) is 20-60 mL / min, and the spray pressure of the atomizer nozzle (5) is 0.4-0.8 MPa.
4. A pelletizing device for improving the performance of tantalum powder as claimed in claim 1, characterized in that: The granulating device comprises a granulating body (7), a vibration motor (9) and a base (10); the bottom of the granulating body (7) is connected to the base (10); the vibration motor (9) is arranged in the granulating body (7); and a storage cylinder (71) is arranged on the granulating body (7).
5. A pelletizing device for improving the performance of tantalum powder as claimed in claim 4, characterized in that: An eccentric shaft A (8) and an eccentric shaft B (11) are arranged on the driving shaft of the vibration motor (9); the eccentric shaft A (8) and the eccentric shaft B (11) are located below a storage barrel (71); the storage barrel (71) is made of stainless steel; an opening is arranged at the top of the storage barrel (71).
6. A method for using the pelletizing device for improving the performance of tantalum powder as claimed in any one of claims 1 to 5, characterized in that: The steps include: 1) Loading tantalum powder raw material into a granulating device, loading a pelletizing agent into a storage container (4) of a spraying device, and simultaneously starting the granulating device and the spraying device to spray the pelletizing agent for the first time and granulate; 2) sieving the wet tantalum powder obtained in step 1), and pouring out the powder on the sieve for later use; 3) the undersize powder obtained in step 2) is loaded into a granulating device, and the spheroidizing agent is loaded into a storage container (4) of a spraying device, and the granulating device and the spraying device are started at the same time to spray and add the spheroidizing agent for the second time and granulate; 4) sieving the wet tantalum powder obtained in step 3), and pouring out the sieved powder for later use; 5) The second undersize powder obtained in step 4) is loaded into a granulating device, and the spheroidizing agent is loaded into a spraying device, and the granulating device and the spraying device are started at the same time, and the spheroidizing agent is added by spraying for the third time and granulating; 6) sieving the wet tantalum powder obtained in step 5), and pouring out the sieved powder for later use; 7) pouring the oversize powder 1 obtained in step 2), the oversize powder 2 obtained in step 4), the oversize powder 3 obtained in step 6) and the undersize powder 3 obtained in step 6) into a granulating device for mixing; 8) Screening the wet tantalum powder after mixing in step 7), and drying after all the powder is screened; 9) The dried tantalum powder is subjected to heat treatment, and after the heat treatment, the tantalum powder is crushed and sieved to obtain pelletized tantalum powder.
7. The method for using the pelletizing device for improving the performance of tantalum powder according to claim 6, characterized in that: The tantalum powder raw material in step 1) is in ppm, and the chemical impurity content in the tantalum powder raw material includes: O≤4500, N≤100, C≤20, Fe≤20, Ni≤15, Cr≤15; the physical property index level of the tantalum powder raw material: the bulk density is 0.8-1.3g / cm 3 ; The average particle size of Fisher is 0.8-1.5μm; The pelletizing agent includes deionized water or deionized water containing any one or more of the dopants NH4H2PO4, (NH4)2HPO4, H3PO4, and NH4PF6; In the step 1), the charging ratio of tantalum powder to pelletizing agent is 0-20 ml / kg; In the step 3), the charging ratio of tantalum powder to pelletizing agent is 0-15 ml / kg; In the step 5), the charging ratio of tantalum powder to pelletizing agent is 0-10 ml / kg.
8. The method for using the pelletizing device for improving the performance of tantalum powder according to claim 6, characterized in that: In the steps 1), 3) and 5), the water spraying amount of the spraying device is 2-10% of the weight of the tantalum powder, and the granulation time of the granulation device is 1-15 minutes; The vibrating screening equipment in steps 2), 4) and 6) is a rotary vibrating screen, the vibration frequency of the rotary vibrating screen is 1200-1600r / min, and the mesh size is 50 or 60 mesh; the vibrating screening equipment in step 7) is a rotary vibrating screen, the vibration frequency of the rotary vibrating screen is 1200-1600r / min, and the mesh size is 40 or 50 mesh; the drying temperature in step 8) is 100-150°C, the drying time is 8-15h, and the drying temperature is 1×10 -1 Pa-1×10 2 The deionized water in the tantalum powder is removed under a pressure of Pa; the heat treatment in step 9) is carried out under a vacuum degree of less than 5×10 -3 The heat treatment is carried out under a vacuum degree of Pa, and the temperature is 1000-1600°C for 60-180min. The heat treatment can be divided into three stages: firstly heating to 600-800°C, keeping warm for 30-120min, then heating to 1000-1200°C, keeping warm for 30-120min, and then heating to 1400-1600°C for 30-120min.
9. Tantalum powder prepared by a pelletizing device for improving the performance of tantalum powder according to any one of claims 1 to 8, characterized in that: The specific capacitance of the tantalum powder is between 8000uF·V / g and 20000uF·V / g.
10. A tantalum anode or capacitor prepared from the tantalum powder as claimed in claim 9.
Citation Information
Patent Citations
Device for granulating tantalum powder and method for manufacturing coagulated tantalum powder through granulation
CN102806345A
Grouped tantalum powder, preparation method thereof and tantalum electrolytic capacitor
CN117733137A
Method for producing titanium powder aggregates
CN1238251A
Granulation method of tantalum powder
JP3105294B2
Tantalum aggregated particles and method for producing the same
JP5183145B2